Polya's Approach to Analyze Students' Errors in HOTS Mathematics’ Story Problems: Case Study in Elementary Schools - Dewi Rahmawati Noer Jannah; Gunarhadi; Riyadi (Universitas Pendidikan Ganesha, 2024)
Numerous elementary school students encounter significant challenges in understanding and solving Higher Order Thinking Skills (HOTS) story problems, particularly in the area of fractions, which require analytical and critical thinking. This study aims to analyze the types of errors made by students when addressing HOTS story problems, with a focus on the differences between Field Dependent (FD) and Field Independent (FI) cognitive styles. The Polya approach is utilized as a framework to comprehend how each step in problem-solving is executed by the students. This research employs a qualitative method with a case study design, involving four fifth-grade students selected through purposive sampling techniques. Data collection is conducted through tests, in-depth interviews, and documentation, which are subsequently analyzed using interactive analysis techniques. The findings indicate that students with a FD cognitive style frequently struggle with understanding the problems and formulating appropriate solution plans, while FI students tend to perform better in these stages but still face challenges in verification and constructing accurate final answers. The findings of this research indicate that students with a Field Dependent (FD) cognitive style tend to struggle with understanding problems and formulating solutions, while those with a Field Independent (FI) style perform better in these stages but still encounter challenges in verifying and accurately organizing their final answers.